2018
DOI: 10.3389/fmicb.2018.03045
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Is a Major Contributor to Adiposity in Pigs

Abstract: Different breeds of pigs vary greatly in their propensity for adiposity. Gut microbiota is known to play an important role in modulating host physiology including fat metabolism. However, the relative contribution of gut microbiota to lipogenic characteristics of pigs remains elusive. In this study, we transplanted fecal microbiota of adult Jinhua and Landrace pigs, two breeds of pigs with distinct lipogenic phenotypes, to antibiotic-treated mice. Our results indicated that, 4 weeks after fecal transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 48 publications
2
68
0
1
Order By: Relevance
“…It is important in animal production to maintain microbial homeostasis using various strategies, such as optimizing animal diets and ensuring appropriate zoohygienic conditions. Suitable microbiota in the pig gastrointestinal tract can ensure increased health status and thus correct or increased production indices [11,54,[90][91][92].…”
Section: Effect Of Diet On Swine Microbiota and Its Influence On Prodmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important in animal production to maintain microbial homeostasis using various strategies, such as optimizing animal diets and ensuring appropriate zoohygienic conditions. Suitable microbiota in the pig gastrointestinal tract can ensure increased health status and thus correct or increased production indices [11,54,[90][91][92].…”
Section: Effect Of Diet On Swine Microbiota and Its Influence On Prodmentioning
confidence: 99%
“…The microbiota of the digestive system not only play a protective role, but can also influence the production parameters of pigs. Changes in the microbiota of the digestive system affect assimilation of nutrients, and in the case of fattener pigs, also the quality and quantity of meat [4,91]. The study by Park et al [4] showed changes in the composition of microorganisms at the genus level between individuals characterized by high meat quality and those with low meat quality.…”
Section: Effect Of Diet On Swine Microbiota and Its Influence On Prodmentioning
confidence: 99%
“…Particularly, bacterial taxa such as Christensenellaceae , Oscillibacter , Defluviitaleaceae incertae sedis , Cellulosilyticum , and Corynebacterium have been positively related to feed efficiency [8], which is critical for the swine industry. Recent studies have also filled some knowledge gaps of the swine gut microbiome, with respect to the biogeography of the gastrointestinal tract [5], adiposity [3], digestibility [4], and growth performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the swine gut microbiome correlated with feed efficiency, fat deposition, and growth performance. [6][7][8][9][10] Despite this progress toward understanding the swine gut microbiome, many important ecological questions are yet to be answered.…”
Section: Introductionmentioning
confidence: 99%